Evaluation of Waste Anesthetic Gas in the Postanesthesia Care Unit within the Patient Breathing Zone - Kenneth N. Hiller; Alfonso V. Altamirano; Chunyan Cai; Stephanie F. Tran; George W. Williams (Anesthesiology Research and Practice)
Potential health hazards from waste anesthetic gases (WAGs) have been a concern since the introduction of inhalational anesthetics into clinical practice. The potential to exceed recommended exposure levels (RELs) in the postanesthesia care unit (PACU) exists. The aim of this pilot study was to assess sevoflurane WAG levels while accounting for factors that affect inhalational anesthetic elimination. In this pilot study, 20 adult day surgery patients were enrolled with anesthesia maintained with sevoflurane. Following extubation, exhaled WAG from the patient breathing zone was measured 8 inches from the patient’s mouth in the PACU. Maximum sevoflurane WAG levels in the patient breathing zone exceeded National Institute for Occupational Safety and Health (NIOSH) RELs for every 5-minute time interval measured during PACU Phase I. Observed WAGs in our study were explained by inhalational anesthetic pharmacokinetics. Further analysis suggests that the rate of washout of sevoflurane was dependent on the duration of anesthetic exposure. This study demonstrated that clinically relevant inhalational anesthetic concentrations result in sevoflurane WAG levels that exceed current RELs. Evaluating peak and cumulative sevoflurane WAG levels in the breathing zone of PACU Phase I and Phase II providers is warranted to quantify the extent and duration of exposure.